Amino acids, glucose metabolism and clinical relevance for phenylketonuria management - Pena, MJ (2015)
It is general knowledge that glycaemia is affected by digested nutrients. Amino acids intake appears to be an important regulator in this regard. Many questions need to be answered, such as the real mediators of this response and the mechanisms underlying this metabolic behavior. Studies have been undertaken in order to investigate the role of amino acids on metabolic parameters. Their main fndings suggest that the ingestion of free amino acids have a pivotal role in avoiding glycaemia excursions, improving glucose tolerance. In parallel, several important molecules for glucose metabolism have been exploited. Insulin and glucagon-like peptide - 1 (GLP-1) release seem to be the main triggers of this response. This insulinogenic effect is attributed to some amino acids, particularly the branched-chain amino acids (leucine, isoleucine and valine). GLP-1 may exert its effects by activating its receptor in pancreas and enhancing insulin release by β-cells or through its extrapancreatic actions. The mechanisms that may justify the aforementioned effects remain to be answered, being the mTOR pathway activation a possible key. These metabolic effects may have a special interest within the nutritional management of Phenylketonuria (PKU), an inborn metabolic disease of phenylalanine (Phe) catabolism. Since a Phe restricted diet is the mainstay of PKU treatment, a chronic supplementation with a Phe-free amino acid mixture is used. Although scientifc evidence is scarce, it is hypothesized whether this chronic ingestion may modulate glycaemia.